Um método para avaliação de desempenho de transmissão em cabos LAN - Escher, Bruno Grinholli [UNESP] (2015)
In cable industry, the LAN network cables quality is knew only in the end of prodution line, measuring the performance of finished cable. So thus, there is a deficiency on quality system, unable to evaluate the intermediate materials before cable layup. This paper proposes a new mathematical tool for handling signal reflection measurements (Return Loss) in high frequencies over the semi-finished ones, in order to guide factory about the quality before going forward on production flow. This method uses the between curves of return loss of twisted pair and the curve of normative limits, being this area the Margin Area (MA). It was verified a great correlation (using Spearman method) between pairs MA and final cable's MA, with and errors chance bellow 1%. Using such MA to select twisted pairs, there were laid up stranded cores with different performances. For automatic MA evaluation, it was also developed the software SATLER for mathematical processing of measurements